(untitled) (Conferencea, 2024)
This article explores the critical role of public officials adhering to ethical principles in the fight against corruption. It highlights how the ethical conduct of government employees serves as a foundation for promoting transparency, accountability, and justice within public institutions. The piece discusses the importance of moral values such as honesty, responsibility, and fairness in reducing corrupt practices. Additionally, it examines the role of leadership, public service ethics, and institutional frameworks in fostering a culture of integrity. By adhering to these ethical principles, public officials can play a significant part in restoring public trust and contributing to effective governance. The article also explores practical recommendations for enhancing ethical behavior within government structures to effectively combat corruption.